IoT-Based a Control System for Household Waste Management Machines at Waste Disposal Sites using Human Machine Interface Method - pawenary, Pawenary; Hendri, Hendri; Listiawati, Dwi; Hardyanti, Andi Dyah Harum; Asri, Yessy; Prabuwono, Anton Satria (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 15 No 03 (2024): Vol.15, No. 3 December 2024DO - 10.24843/LKJITI.2024.v15.i03.p02, 2025)
To manage waste efficiently and sustainably , Integrating Algoritma Bellman-Ford in IoT-Based Control Systems for Household Waste Management Machines, the use of automation technologies based on the Internet of Things (IoT) is becoming increasingly relevant. The integration of HMI allows operators to manage and control the machine with precision and convenience. The synergy between IoT and HMI promises significant improvements in waste processing speed, accuracy, and safety. Developing a control system using the HMI method is not just a solution but an innovative approach that aims to find an effective solution in managing or destroying waste that requires less labor, so there is no need to increase assistance. The method that will be used in this research is the descriptive statistical method, namely, assessing the technical data needed to develop a control system that complies with the standard. This innovative approach is one of the solutions to the problem of labor shortages in landfills that simplify work and speed up the process of operating machines.